The impacts of household retrofit and domestic energy efficiency schemes: A large scale, ex post evaluation. (September 2015) - Webber, Phil; Gouldson, Andy; Kerr, Niall
Abstract: There is widespread interest in the ability of retrofit schemes to shape domestic energy use in order to tackle fuel poverty and reduce carbon emissions. Although much has been written on the topic, there have been few large-scale ex post evaluations of the actual impacts of such schemes. We address this by assessing domestic energy use before and after the Kirklees Warm Zone (KWZ) scheme, which by fitting insulation in 51, 000 homes in the 2007–2010 period is one of the largest retrofit schemes completed in the UK to date. To do this, we develop and apply a new methodology that isolates the impacts of retrofit activity from broader background trends in energy use. The results suggest that the actual impacts of the KWZ scheme have been higher than predicted, and that the scale of any performance gaps or rebound effects have been lower than has often been assumed. They also suggest that impacts on energy use in lower income areas are consistent with predictions, but that impacts in middle and higher income areas are higher than predicted. These findings support the case for the wider and/or accelerated adoption of domestic retrofit schemes in other contexts. Highlights: A large scale, ex post evaluation of the impacts of a household retrofit scheme. A new methodology to separate retrofit impacts from background trends. Shows impacts of retrofit have been 1.2–1.7 times higher than predicted. Impacts as predicted in lower income areas, higher in middle and upper income areas. Findings support the case for the wider and faster adoption of domestic retrofit.